Four new species of Xenotarsonemus (Acari: Tarsonemidae) from Brazil - Lofego, Antonio C.; de Moraes, Gilberto J.; Ochoa, Ronald (Zootaxa, 2007)
Four new species of Xenotarsonemus Beer (Acari, Tarsonemidae), X. brachytegula, X. pirassunungaensis, X. cerrado and X. spiniphorus, are described based on specimens collected from plants of the "Cerrado" vegetation in the State of São Paulo, Brazil.